Augmented Reality in Health Comics: GermBusters VR Media Development for Children's Health Learning in Elementary Schools - Bintartik, Lilik; Irawan, Dani; Thohir, M. Anas; Naili, Khomsiyah; Oktaviani, Sabillatush (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Augmented Reality (AR) technology has become an important innovation in the world of education, especially in increasing students' interest and understanding. This study aims to develop Augmented Reality-based health comics as educational media for children's health learning in Elementary Schools. This study uses the Research and Development (R&D) method with the ADDIE model. The subjects of the study involved two experts, three teachers, and 42 3rd grade students from three elementary schools in Malang City, namely SD Tunggulwulung, SD Kebonsari, and SD Sukun 2. Students were selected using purposive sampling techniques. Data collection techniques used questionnaires and assessment scales. Data analysis was carried out descriptively. The results of the study showed that: 1) at the design stage, an initial product of AR-based health comics was developed with the nameGermBusters VR; 2) the validation results from experts show that this product is very feasible to be used in health learning; 3) the teacher and student response questionnaires indicate that this AR-based comic is very practical and interesting to be used as a health learning medium.